ANALISIS PENERAPAN ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) DALAM MENINGKATKAN EKO-EFISIENSI USAHA (Studi Kasus Pada Rumah Sakit Ibnu Sina YW-UMI Kota Makassar) - Indrawan Azis; Andi Widiawati; Annisa Aprilia Nur (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
Current issues related to the environment to be one of the issues that got the attention of the public. Awareness of the community to participate in protecting the environment is increasing from time to time. It encourages businesses as part of the community itself, to participate in maintaining the environment in ways that minimize the risk of environmental damage as a result of the operational company's. In this case, the needed cost of the so-called environmental costs. Environmental costs necessary to achieve eco-efficiency efforts, one of which is the use of Environmental Management Accounting (EMA), by identifying environmental costs by classifying into the category of environmental quality to evaluate their environmental performance. This study uses the Ibnu Sina Hospital YW-UMI Makassar City engaged in health services as research objects. In this study the author uses descriptive qualitative method. The results showed that the Ibnu Sina Hospital YW-UMI Makassar City yet to implement Environmental Management Accounting (EMA), manage environmental costs, but this hospital has managed the impact of the environment.